The Role of Religious Behavior in Health Self-Management: A Community-Based Participatory Research Study - Pfeiffer, Jane (Religions, 2018)
Prevalence of chronic disease, mental health problems, and risk behaviors in San Bernardino (SB) County reflect some of the worst health outcomes in the State of California and the United States. Using the Integrated Theory of Health Behavior Change (ITHBC) as the theoretical framework, this community-based participatory research (CBPR) study aimed to determine how religious self-regulation skills and ability, and religious behaviors, jointly affect health promotion behaviors among socio-economically challenged residents of southwest SB County, California. A convenience sample of adult residents (N = 261) completed a series of inventories to measure the relationship between modified ITHBC constructs of religious self-regulation skills, religious self-management behaviors, and health outcomes. Structural Equation Modeling (SEM) analysis was conducted to validate the strong positive effect of religious self-regulation skills and ability on how frequently individuals engage in both organized and non-organized religious activities. Results also indicated a significant positive impact of religious behaviors towards healthy eating behaviors. However, without the engagement in religious activities, high religious self-regulation skills and ability inhibited the likelihood of healthy food intake. This faith-related theoretical model provides an avenue for faith-based organizations' capacity for contributing to community health promotion.